Investigation of Symmetrical Modes of Operation and Calculation of the Installed Capacity of Phase-Shifting Transformer, Based on Hexagon Connection - Bosneaga V.; Suslov V. (Problems of the Regional Energetics)
The scope of the work is to study the steady-state symmetrical load modes of operation of a new promising phase-regulating transformer circuit. This allows obtaining the value of the designed capacity of device. The device is based on a three-phase transformer windings connection into hexagon circuit, equipped with additional three phase regulating autotransformer, connected to hexagon circuit in a special manner. Besides, it should be equipped with semi-conductor switching keys, which give the possibility to control fast transition processes. The proposed circuit gives the possibility to round regulation of phase angle in the range of 0-360°, so the device could be used as frequency converter for flexible tie between energy systems with different frequencies and belongs to the group of FACTs controllers. The autotransformer provides the possibility of fine adjustment of the phase angle of the output three-phase voltage, so maintaining the flow of active power in the interconnection line. One of the most important features of such devices is the value of calculated designed capacity, which determines demand of the active materials for such devices. The scope of the work was achieved by conducted analytical study, based on electrical and transformer circuit’s theory. The currents in the windings of the device in symmetrical load modes were calculated for several variants of the phase-regulating unit circuit’s diagrams. On their basis, the maximum values of the devices currents and designed capacity for a number of the considered variants of circuits were determined, allowing a comparative analysis of different circuit modifications.